NILAI PERUSAHAAN SUB SEKTOR FARMASI & RISET KESEHATAN YANG DIPENGARUHI PROFITABILITAS, LIKUIDITAS, LEVERAGE - Dimas Triyanto; Zulfikar Ramadhan (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study aimed to determine and analyze the influence of profitability, liquidity, and leverage on the value of pharmaceutical and health research companies listed on the Indonesia Stock Exchange (IDX). This research is a quantitative, associative study. The population of this study was pharmaceutical and health research companies listed on the Indonesia Stock Exchange in 2021-2024. Purposive sampling was used to select 11 companies.The analysis method used in this study is multiple linear regression analysis on panel data, namely by determining the estimation model, estimation method, determination coefficient test and hypothesis test.The results of the study indicate that profitability has a positive but insignificant effect on firm value, liquidity has a positive but insignificant effect on firm value, and leverage has a positive and significant effect on firm value. These findings indicate that investors in the pharmaceutical subsector place more importance on a company's funding structure than on its ability to generate profits and meet short-term obligations. This research is expected to contribute to the development of financial management literature and serve as a consideration for investors and company management in making financial decisions.Keywords: Firm Value, Profitability, Liquidity and Leverage